IR SPECTROSCOPIC ANALYSIS OF BENZENE-1,4-DICARBOXYLIC ACID ("Conference on Universal Science Research 2023", 2025)
In this scientific work, we will get acquainted with the results of comparing the theoretical and practical results of the infrared spectroscopic analysis of benzene dicarboxylic acids belonging to the carboxyl group